Legal Responsibilities of Educational Institutions in Cases of Plagiarism within College Environment - Sholeh, Muh. Ibnu; 'Azah, Nur; Sholihan, Sholihan; Arifin, Zainur; Sokip, Sokip; Syafi'i, Asrop; Sahri, Sahri (Civiliza Publishing, 2024)
This study examines the legal responsibilities of colleges in managing plagiarism cases within their contexts. The primary aim is to evaluate the effectiveness of internal regulatory frameworks related to plagiarism, the role of detection technology, the level of awareness within the academic community, case management practices, and the potential legal consequences. The research employs a library research methodology with a descriptive-analytical framework, involving an extensive review of literature and analysis of institutional policies. The findings reveal that while many colleges have established internal regulations to address plagiarism, there are significant deficiencies in their implementation, particularly concerning policy dissemination and enforcement of sanctions. Plagiarism detection technologies, such as Turnitin, are crucial for identifying instances of academic misconduct; however, their effectiveness depends on the proper understanding and application by both faculty and students. The study also highlights variations in the understanding of plagiarism among students and faculty, emphasizing the need for more comprehensive and nuanced educational programs.